The influence of interactive learning, learning motivation, immersion learning and cognitive learning on learning performance - Li-Wei Lin; Shih-Yung Wei; Kuo-Liang Lu; Shuo Wang; Tai-Ge Yan (Humanities & Social Sciences Communications)
Abstract Faced with the impact of COVID-19 in mainland China in 2022, many universities adopted a hybrid approach, combining online and offline teaching. However, limited research has been conducted on hybrid education. Our study primarily investigated college students in mainland China, examining the effectiveness of hybrid teaching through a questionnaire survey on their learning performance. Due to the recurring outbreaks, many universities continued to implement blended teaching. Our research aimed to develop new models to explore the relationships between students’ interactive learning, learning motivation, immersion learning, cognitive learning, and overall learning performance. We sought to enhance students’ learning outcomes through mixed learning approaches. Our study surveyed N = 387 students, and three hypotheses were found to be positively correlated. Using statistical analysis, we estimated the overall learning rate and examined the relationships among key causal variables. The results indicated that learning motivation and immersion learning are positively correlated with cognitive learning, which, in turn, cognitive learning is positively correlated with learning performance. A significant finding of our research is that students prefer a hybrid learning model that integrates online and offline learning methods.